A poesia sem estrela de Zuca Sardan: uma leitura de ás de colete - Bazanella, Deise Daiana Gugeler (2011)
In the 1970 s, Brazilian marginal poetry broadened the communicative levels of the poetic text in order to attract more readers. To achieve that, it questioned the traditional procedures of modern lyric poetry, thus making explicit a series of changes in contemporary sensitivity and creating difficulties to established critical approaches. In this period of paradigms rupture we find the poet Zuca Sardan, whose book, Ás de Colete (originally published in 1979 and re-edited by Editora da Unicamp in 1994), is the object of reflection in this work. Aiming at discussing some of its characteristics, I propose a reading based on the concept of antipoetry, which helps to understand the sardanian poem as a hybrid discourse based on some of its most prominent aspects: image, humor and communicative form (effect of the strategic use of resources commonly associated to prose), conjugated in order to produce a revealing and unusual estrangement effect on the reader s perception.